THE EFFECT OF TRAVEL DESTINATION PRICES AND INCOME ON SEA TRANSPORTATION CROSSINGS (CASE STUDY OF MANADO PORT ROUTE - TALAUD ISLANDS REGENCY) - Obet L Unsong; Christian Mangode (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims to determine the effect of travel destinations and income on the demand for inter-island crossing transportation services on the Manado-Talaud Islands Regency route. This study uses a quantitative approach with a survey method through a questionnaire to 60 respondents who are passengers who often travel by ship from Manado to Talaud. The results of the study indicate a partial effect on price, travel destination, income and price variables that occur in sea transportation crossings at Manado Port to Talaud Islands Regency